Sensitive ergotamine determination in pharmaceuticals and biological samples using cloud point preconcentration and spectrofluorimetric detection - Wang, Chien Chun (2013)
A new cloud point extraction (CPE) method for ergotamine analysis using fluorimetric detection is described. Ergotamine from an aqueous solution was preconcentrated into a smaller surfactant-rich phase using nonionic surfactant polyoxyethylene(7.5)nonylphenylether (PONPE 7.5). Differently from the conventional CPE procedure in which the resulting surfactant-rich phase is diluted by a fluidificant before its analysis, in this method the fluorescence measurements were carried out directly onto the undiluted surfactant-rich phase. The high viscosity provided by the undiluted surfactant rich phase greatly improved the fluorescence emission of ergotamine, leading to a total enhancement factor of 1325. This spectral advantage plus the preconcentration factor achieved, contributed to the method sensitivity allowing the ergotamine determination at trace level concentration. Under optimal experimental conditions, a linear calibration curve was obtained from 3.81 × 10−7 to 1.10 μg mL−1, with detection and quantification limits of 0.11 and 0.38 pg mL−1, respectively. The accuracy and versatility of the present methodology were proved by analyzing ergotamine in real samples of different natures such as pharmaceuticals, urine and saliva.